Migrasi dan Perubahan Sosial Masyarakat Suku Bangsa Manggarai di Kota Jayapura - Krispinus H. Sefik; Ferry R.P.P. Sitorus; Urip Wahyudin (Universitas Serambi Mekkah, 2026)
This study aims to understand: (1) Identifying the push and pull factors of the Manggarai ethnic group migrating to Jayapura City. (2) Describing the forms of social change of the Manggarai ethnic group after migrating to Jayapura City. This study uses a qualitative descriptive method. The subjects of this study are the Manggarai ethnic group who migrated to Jayapura. Data collection techniques use interview, observation, and documentation guidelines. Data analysis techniques use the Miles and Huberman model guidelines (Data Reduction, Data Presentation, and Conclusion Drawing). The results of the study show that the factors that influence the Manggarai community to migrate to Jayapura are because agricultural land in the village is limited, job opportunities are lacking, job opportunities are lacking, and income is not enough to meet family needs. Jayapura City was chosen because there are many job opportunities, higher salaries, and the presence of relatives or friends from Manggarai who have already lived in Jayapura. In Jayapura, the Manggarai community experienced changes in life such as from an economic perspective; those who used to depend on their families gradually became more independen, through permanent jobs or their own businesses. In terms of family relationships, decision-making, previously dominated by husbands, is now shared between husband and wife, and inheritance is now distributed fairly to all children, regardless of gender.